Pengaruh Corporate Governance Structure dan Leverage Terhadap Pengungkapan Intellectual Capital - Mujiani, Sari; Wilestari, Median; Putri, Maharani Eka (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2020)
The purpose of this research is to obtain empirical evidence about the effect of independent commissioner, foreign ownership and leverage on intellectual capital disclosure at indeks kompas 100 companies listed in Indonesia Stock Exchange in 2014-2018. This research used a purposive sampling technique to collect data and consisted of 12 companies listed on the Indonesia Stock Exchange in 2014-2018. The statistical method used in this research is used multiple linear regression analysis methods. In this research used the Eviews program, 9 version. The results of the research based on the tests that have been that independent commisioner not had a significant effect on intellectual capital disclosure, while foreign ownership and leverage had a significant positive effect on intellectual capital disclosure.